Pengembangan Modul Mobile Learning Menggunakan Atutor Pada Pembelajaran Fisika Kelas X SMA Negeri 9 Padang Berorientasi Literasi Skill Revolusi Industri 4.0 - Widia Mai Yetri; Pakhrur Razi (Jurnal Ilmu Fisika dan Pembelajarannya (JIFP), 1970)
This research was conducted with the aim to develop a mobile learning module using the industrial revolution 4.0 skill literacy oriented atutor on newton's legal materials as well as effort and energy for the 10th grade of high school. The method used in this research is research and development (R&D) developed by Sugiyono. The stages carried out in this study are limited to 5, namely planning with the identification of potentials and problems, information collection, creating new designs, product validation, and product revisions. The object in this study is the mobile learning module using the atutor oriented skill literacy of industrial revolution 4.0. The data in this study was obtained through a validity instrument consisting of 4 components filled by validators. The value obtained from the validator is analyzed using a formula so that 80.25 results are obtained that are in a very good category. This shows that the mobile learning module using the industrial revolution 4.0 skill literacy oriented atutor is valid.